Performance-based outcomes following patellar tendon repair in professional athletes - Nguyen, M. T.; Hsu, W. K. (The Physician and Sportsmedicine, 2020)
Objectives: There are limited data on the impact of a patellar tendon repair to a professional athlete`s career. The purpose of this study was to determine differences return to play (RTP) rate, career length, and performance-based outcomes after a patellar tendon repair in professional athletes of four different sports.